2023
DOI: 10.1002/lpor.202300286
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals Integrated LiNbO3/WS2 for High‐Performance UV–Vis–NIR Photodetection

Abstract: Lithium niobate (LN) is widely used in various optoelectronic systems due to its structural anisotropy and ferroelectric feature, which is one of the most essential platforms for next‐generation integrated optoelectronics. However, the insulating and optically transparent characteristics of LN have greatly limited the application in photodetection. Here, a high‐performance LN/WS2 based photodetector is achieved through a van der Waals integration strategy in which the pyroelectric property of LN and the modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 82 publications
0
0
0
Order By: Relevance
“…At the same time, Si and its oxide SiO 2 both have good light absorption ability, which makes their performance in the bandwidth of the visible and near-infrared regions tend toward perfection [28]. On the other hand, Surface Plasmon Resonance (SPR) due to shape structure has a significant impact on the absorber's performance [29][30][31][32][33]. In previous studies, the emergence of equal-width arranged structures of discs of different sizes [34], stacked structures of complex trapezoidal shapes [35], and regularly arranged structures of elliptic and disc arrays [36] showed that highly absorbing physical properties are the result of both SPR and multiple resonance modes [37].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, Si and its oxide SiO 2 both have good light absorption ability, which makes their performance in the bandwidth of the visible and near-infrared regions tend toward perfection [28]. On the other hand, Surface Plasmon Resonance (SPR) due to shape structure has a significant impact on the absorber's performance [29][30][31][32][33]. In previous studies, the emergence of equal-width arranged structures of discs of different sizes [34], stacked structures of complex trapezoidal shapes [35], and regularly arranged structures of elliptic and disc arrays [36] showed that highly absorbing physical properties are the result of both SPR and multiple resonance modes [37].…”
Section: Introductionmentioning
confidence: 99%